Optimizing Checks and Balances in the Indonesian Government System - Syayyidah, Liza Elyvia Nur (Maliki Interdisciplinary Journal, 2026)
Following the amendment of the 1945 Constitution of the Republic of Indonesia, Indonesia's system of government underwent fundamental changes with the affirmation of the principle of separation of powers and the mechanism of checks and balances as the main instruments for limiting state power. This principle is intended to prevent the concentration of power in a single state institution and to ensure democratic, accountable, and constitutional governance. This study aims to analyze the implementation of the checks and balances mechanism in the Indonesian government system and identify factors that hinder its optimization in constitutional practice. The research method used was normative juridical with a legislative and conceptual approach, through a literature study of the 1945 Constitution, related legislation, Constitutional Court decisions, and literature in the form of books and scientific journals. The results of the study show that, normatively, the checks and balances mechanism has been regulated quite comprehensively through the relationship between the executive, legislative, and judicial branches, and is reinforced by the existence of independent state institutions. However, in practice, this mechanism has not been running optimally. The main obstacles include the dominance of executive power, the weak supervisory function of the legislature due to political configurations and large coalitions, the low independence and professionalism of supervisory institutions, weak compliance with Constitutional Court decisions, and a legal and political culture that does not fully uphold constitutional supremacy. Therefore, optimizing checks and balances requires not only regulatory strengthening, but also political reform, institutional strengthening, and the development of a sustainable constitutional culture.